EFEK MEDIASI KEAHLIAN DALAM PENGARUH LOCUS OF CONTROL DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN - Setyaasih (MANAJEMEN DEWANTARA, 2024)
This study examines the effect of Locus Of Control and Organizational Commitment on the performance of production supervisor-level employees in paper companies in East Java and the mediating role of expertise in the relationship. This study uses a quantitative design with data analysis using SEM PLS (Partial et al. Equation Modeling). The research sample consisted of 125 respondents who were production supervisor-level employees at paper companies in East Java. The results showed that the Locus Of Control variable significantly affects employee performance. In addition, the Organizational Commitment variable also has a significant influence on employee performance. Furthermore, this study found that expertise can mediate the effect of Locus Of Control on employee performance and the effect of Organizational Commitment on employee performance. This research contributes to enriching the understanding of the factors that influence the performance of production supervisor-level employees in paper companies. The results of this study can be used as a basis for developing more effective and efficient human resource management strategies and policies. Keywords : Locus Of Control, Organizational Commitment, Employee Performance, Expertise, Production Supervisor.